AIR conferencing: accelerated instant replay for in-meeting multimodal review - Inkpen, Kori; Hegde, Rajesh; Junuzovic, Sasa; Brooks, Christopher; Tang, John; Zhang, Zhengyou (2010 ACM Multimedia, 2010)
When people attend meetings they may miss parts of the discussion if they, for example, step out to take a phone call, go to the bathroom, or have a momentary lapse in concentration. As a result, they may need to catch up on what they missed upon returning to the meeting. Asking other attendees for a recap is often disruptive. To avoid such disruptions, we have developed an Accelerated Instant Replay (AIR) Conferencing system for videoconferencing that enables participants to privately catch up to an ongoing meeting. We explored several mechanisms where the meeting content is replayed at an accelerated rate so that the participants can catch up to the live discussion reasonably quickly.